Pairwise comparison of hydrochlorothiazide and chlorthalidone responses among hypertensive patients - Lakshmi Manasa S. Chekka; Rhonda M. Cooper‐DeHoff; John G. Gums; Arlene B. Chapman; Julie A. Johnson (Wiley, 2022)
Abstract This study conducted a pairwise comparison of antihypertensive and metabolic effects of hydrochlorothiazide (HCTZ) and chlorthalidone (CTD) at 25 mg/day in the same individuals to address the clinical dilemma on preferred thiazide for hypertension (HTN) management. We included 15 African American (AA) and 35 European American (EA) patients with HTN treated with HCTZ and CTD as part of the Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) and PEAR‐2 trials, respectively. Mean reduction in systolic/diastolic blood pressure (SBP/DBP) with HCTZ versus CTD was 8/5 versus 16/8 mmHg among EA patients (p < 1.0e−5 SBP, p = 0.002 DBP) and 11/8 versus 20/11 mmHg among AA patients (p = 0.03 SBP, p = 0.22 DBP). While CTD showed clinically meaningful benefit over HCTZ in two‐thirds of participants with respect to SBP reduction and half of EA patients with respect to DBP reduction, a majority of AA patients (53%) showed similar DBP reduction with both thiazides. Sixty percent of AA patients and 29% of EA patients attained blood pressure (BP) <140/90 mmHg with both thiazides. Mean potassium (K+) reduction was greater with CTD compared to HCTZ both in EA patients (mean difference = 0.35, p = 0.0002) and AA patients (0.49, p = 0.043). While 31% of AA patients developed severe hypokalemia on CTD, <5% of others developed severe hypokalemia. Although 46% of AA patients on CTD required K+ supplementation, only 6%-11% of others required supplementation. Overall, in the majority of EA patients, CTD was superior to HCTZ, whereas among AA patients, it was superior in a minority, and was associated with significant potassium‐related risk, suggesting that guideline preferences for CTD over HCTZ are reasonable in EA patients but may be less reasonable in AA patients, particularly if the target is <140/90 mmHg.